Recessionary games: Video games and the social imaginary of the Great Recession (2009–2015). (December 2019) - Pérez-Latorre, Óliver; Navarro-Remesal, Víctor; Planells de la Maza, Antonio José; Sánchez-Serradilla, Cristina
How do the most popular video games in recent years contribute to the construction of the social imaginary of the Great Recession? The discursive struggles over the definition of crucial aspects of the recession such as austerity, the heroic ethos to face precariousness and being anti-establishment are being played not only in the political arena and 'serious' news genres but also in the narrations of popular culture and video games. Thus, critical analysis of the social resonances of video games on the Great Recession is a relevant exercise not only academically but also socially. To address this question, this article proposes an analysis of bestselling video games from 2009 to 2015, based on cultural studies and game studies. The analysis is organized in three case studies: (a) post-apocalyptic video games and their potential resonances regarding austerity and precariousness; (b) video games, neo-liberalism and counter neo-liberal views; and (c) video games and the representation of anti-establishment characters and rebel communities.